PENGARUH PENDEKATAN RME TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS DAN KEPERCAYAAN DIRI SISWA - Fariz, Irsyad Nur; Isrok'atun, I.; gusrayani, diah (Jurnal Pena Ilmiah, 2017)
This research is held base on a thought that mathematical representation ability and self confidente can be improved by a good learning. There is one learning methode that suitable for mathematical representation ability and self confident improvement is RME approach. This research is quasi experiment research that used nonequivalent control group design. The sample in this research is 5th grade student at SDN Cimalaka 1 as the experiment class and SDN Palasah as the control class. Instrument that used in this research is test for the result of learning, behavior scale, guidelines of teacher performance observation, and guidelines of student activity observation . This research has result with signification rate = 0,05 (5%) show that RME approach can improve mathematical representation ability and self confident. RME approach is better significantly then conventional approach for improving mathematical representation ability and self confident of the students. There is positif relation between mathematical representation ability and self confident.